Effect of adjunctive dipyridamole to DAPT on platelet function profiles in stented patients with high platelet reactivity - Park, Yongwhi; Jeong, Young-Hoon; Tantry, Udaya S.; Ahn, Jong-Hwa; Kim, Kye Hwan; Koh, Jin-Sin; Park, Jeong-Rang; Hwang, Seok-Jae; Kwak, Choong Hwan; Hwang, Jin-Yong; Gurbel, Paul A. (Thrombosis and Haemostasis, 2014)
Adjunctive use of phosphodiesterase (PDE) inhibitor can enhance antiplatelet and vasoprotective properties in patients with cardiovascular disease. The aim of this study was to evaluate the impact of PDE5 inhibitor dipyridamole on platelet function in stented patients with high platelet reactivity (HPR) during dual antiplatelet therapy (DAPT) with aspirin and clopidogrel. Patients with HPR after 600-mg clopidogrel loading were randomly assigned to adjunctive dipyridamole 75 mg twice daily to standard DAPT (DIP group; n = 45) or double-dose clopidogrel of 150 mg daily (DOUBLE group; n = 46) for 30 days. Platelet function was assessed at baseline and 30-day follow-up with platelet reactivity index (PRI) by vasodilator-stimulated phosphoprotein-phosphorylation (VASP-P) assay and platelet aggregation (PA) by light transmittance aggregometry (LTA). Primary endpoint was PRI at 30-day follow-up. HPR was defined as PRI > 50%. Baseline platelet function did not differ between the groups. Following 30-day therapy, platelet function was significantly reduced in the DIP and DOUBLE groups (all p-values ≤ 0.004 and ≤ 0.068, respectively). PRI values were not significantly different between the two groups (mean difference: 3.1%; 95% confidence interval: –2.8% to 9.0%: p = 0.295). PA values and prevalence of HPR were similar between the groups. However, a significant number of patients still exhibited HPR in the DIP (75.6%) and DOUBLE (67.4%) groups. In conclusion, among stented HPR patients, adding dipyridamole to DAPT does not reduce platelet reactivity and prevalence of HPR compared with double-dose clopidogrel therapy, and therefore both strategies are inadequate to overcome HPR.
Keywords: Platelets; dipyridamole; clopidogrel; intervention